Do fair procedures matter? The effect of procedural justice on spouse assault. - Paternoster, Raymond; Brame, Robert; Bachman, Ronet (Law & Society Review, 1997)
The writers reanalyzed the Milwaukee Domestic Violence Experiment in order to investigate whether the use of fair procedures on the part of police officers called to the scene of a domestic assault inhibits subsequent assault. As they had expected, procedural justice curbed subsequent violence, even in the face of adverse outcomes. Their analysis revealed that when police acted in a procedurally fair manner in arresting assault suspects, the rate of subsequent domestic violence was significantly lower than when they did not act in a fair manner. In addition, arrested suspects who perceived that they were treated in a procedurally fair manner had subsequent assault rates that were as low as those of suspects who were given a more favorable outcome, that is, warned and then released without arrest. The writers observed that the suppression effect of procedural justice was not dependent on the personal temperament of suspects.